Experimental fire response of seismic elastomeric bearings. (1st March 2022) - Lucon, Massimiliano; Baragatti, Paolo; Possidente, Luca; Tondini, Nicola
Highlights: Fire tests on protected and unprotected seismic rubber bearings. Pre- and post-fire mechanical characterisation under axial loading. A comprehensive discussion about the fire behaviour of the bearings. Unprotected rubber bearing met the 60 min fire resistance. Protected rubber bearings met the 90 min fire resistance. Abstract: The paper presents the results of an experimental campaign conducted with the aim to evaluate the fire behaviour of unprotected and protected seismic elastomeric bearings installed inside an actual building. In particular, one unprotected and two protected natural rubber bearings were tested under the ISO 834 heating curve. The fire protection was made of blankets based on alkaline earth silicate wools (AES) of different thickness, i.e. 100 mm and 125 mm. The fire tests were performed by applying a constant vertical load equal to 900 kN to elastomeric bearings of diameter 400 mm, i.e. applied stress less than 10 MPa. The tests highlighted that the unprotected elastomeric bearing met the fire resistance requirement of 60 min before a loss of vertical load-bearing capacity owing to degradation of the mechanical properties at elevated temperature, whereas the protected elastomeric bearings could satisfy the fire resistance requirement of 90 min. A comprehensive description of the experimental outcomes, that also include the characterisation of the residual post-fire mechanical properties, is thoroughly reported in the paper.